How can HOTS for Vocational High School Students be Enhanced through the Problem-Based Learning model? - Lilik Sri Hariani; Mua’azam bin Mohamad; Sulistyo Sulistyo (AL-ISHLAH: Jurnal Pendidikan, 2023)
Problem-based learning (PBL) aims to enhance students' engagement, creativity, and technological proficiency by offering them autonomous learning experiences. The comprehensive approach to PBL entails acquiring knowledge through collaborative project work and using real-life experiences. This method has demonstrated its ability to foster both academic and soft skills. The study aims to examine the role of a scientific-based problem-based learning model (PBL) in improving the higher-order thinking skills (HOTS) of students in vocational high schools. The study employed a quantitative approach with a quasi-experimental method, with a total of 56 students in both experimental and control classes. The data was analyzed using the t-test and the n-gain test. The results of the study show that (1) the scientifically based problem-based learning model is effective in improving higher-order thinking skills in vocational high school students; (2) the knowledge transfer indicators in experimental classes have the highest scores, critical thinking indicators in medium categories, and problem-solving indicators in medium categories. In conclusion, PBL greatly contributed to improving students' 21st-century skills.